Next Generation Sequencing for Diagnosis of Leptospirosis Combined With Multiple Organ Failure: A Case Report and Literature Review - Lu, Juan; Hu, Juan; Yu, Shanshan; Li, Lanjuan (Frontiers in Medicine, 2022)
Introduction Leptospirosis poses a major threat to human life. The disease spectrum ranges from a nearly undetectable presentation to severe multi-organ dysfunction and death. Leptospirosis is difficult to diagnose by traditional antibody and culture tests. We here present a case of multiple organ failure associated with leptospirosis. Material and Methods A 64-year-old woman presented with fatigue and arthralgia, which developed rapidly into multiple organ injuries, and she eventually died of cerebral hemorrhage. Serum antibody test and cultures of blood, sputum, urine, and feces samples were all negative. The patient was diagnosed with leptospirosis by the next-generation sequencing (NGS). Conclusion We conclude that leptospirosis is a neglected zoonosis caused by pathogenic Leptospira species. New techniques such as NGS are highlighted for early diagnosis. Surveillance for pathogens during diagnosis can provide guidance for clinical treatment and improves prognosis.